2005
DOI: 10.1016/j.adnc.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The Primacy of Work and Fathering Preterm Infants

Abstract: Fathers may respond to the experience of having a premature infant very differently from mothers. Because fathers' stressors often lie outside the NICU, their stressors may be invisible to healthcare providers. A deeper understanding of fathering must consider the social, familial, and historical processes that shape fathering practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 36 publications
3
34
1
5
Order By: Relevance
“…Finalmente, algunos padres identificaron de pleno su rol paternal con su rol de proveedores, es decir, para ellos ser padres significaba ser el responsable del sustento económico familiar (Pohlman, 2005) bien por convicciones y creencias propias, bien porque seguían el modelo heredado de sus propios padres.…”
Section: Estrategias De Afrontamientounclassified
See 2 more Smart Citations
“…Finalmente, algunos padres identificaron de pleno su rol paternal con su rol de proveedores, es decir, para ellos ser padres significaba ser el responsable del sustento económico familiar (Pohlman, 2005) bien por convicciones y creencias propias, bien porque seguían el modelo heredado de sus propios padres.…”
Section: Estrategias De Afrontamientounclassified
“…La función protectora y proveedora, sin embargo, los mantiene alejados del contacto con su bebé (Arockiasamy et al, 2008;Feeley, Sherrard, Waitzer, & Boisvert, 2013;Hugill et al, 2013;Pohlman, 2005), bien porque no tienen tiempo, bien porque doi:10.11600/1692715x.16102 creen que los cuidados del hijo deben recaer exclusivamente en la madre.…”
Section: Roles De Génerounclassified
See 1 more Smart Citation
“…Several researchers have investigated the experiences of mothers of preterm infants (Aagaard & Hall, 2008;Davis, Edwards, Mohay, & Wollin, 2003;Hall & Brinchmann, 2009;Holditch-Davis & Miles, 2000). There is currently a lack of studies that have focused exclusively on the father's experiences in connection with the birth of a preterm infant and longitudinally, but this situation is slowly improving (Lundqvist & Jakobsson, 2003;Lundqvist, Westas, & Hallstrom, 2007;Pohlman, 2005Pohlman, , 2009Sloan, Rowe, & Jones, 2008). It has been shown that caring for a preterm infant in a NICU is stressful for fathers; they have reported feelings of worry related to their infant's preterm birth, concern for their partner and difficulties in prioritizing their roles as partner, father and breadwinner (Arockiasamy, Holsti, & Albersheim, 2008;Lundqvist et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Esta reação é descrita na literatura como uma das principais reações apresentadas pelo casal parental (Hall, 2004;Watson, 2010). Estudos somente com pais homens mostram que os pais se sentem impotentes por não se sentirem capazes de fazer algo para proteger o filho (Pohlman, 2005). Para Watson (2010), a transição para a parentalidade só se fortalece quando os pais sentem que têm controle sobre a situação.…”
Section: Sentindo-se Em Um Campo De Guerraunclassified